High prevalence of Bordetella pertussis in severe acute respiratory infections in hospitalized children under 5 years in Lima, Peru - Pavic Espinoza, Ivana (2015)
ASTMH 64th Annual Meeting. October 25-29, 2015 Philadelphia Marriott Downtown Philadelphia, Pennsylvania USA